Morphometric analysis of lateral menisci in North Indian population: a cadaveric study - Rohila, Jyoti; Rathee, Suresh Kanta; Bansal, Swati (International Journal of Research in Medical Sciences, 2017)
Background: The menisci (formerly called semilunar cartilages) of the knee lie within the knee joint between the femur and tibia and somewhat adapt the tibial and femoral condyles to each other. The menisci are liable to injury resulting from twisting strains applied to flexed weight bearing knee. The mean annual incidence of meniscal tears is about 60-70 per 100,000 with a male to female ratio ranging from 2.5:1 to 4:1. The present study was conceived to provide valuable morphological data for preparing meniscal allograft for people of this region so that accurate matching can be done in meniscal transplantation. Methods: The study was carried out in 100 lateral menisci of adult human male cadavers with age ranging from 20 to 50 years. Distance between anterior and posterior horns of lateral meniscus, outer and inner border length, width and thickness at three points, namely anterior, middle and posterior one third was taken with the help of non-elastic thread and Vernier caliper. Written informed consent was taken from the relatives of the deceased. Results: Distance between the two horns of lateral meniscus, outer border and inner border length of right and left lateral meniscus were not significantly differently from each other. Width and thickness of lateral meniscus was highest in the middle part which was significantly different from other parts. Conclusions: In conclusion, width and thickness was highest in the middle third part of lateral menisci. Also, shapes of lateral menisci were different from others studies. The current study presents a database of morphological values of lateral menisci for North Indian population for meniscal transplantation.